Potensi Jamur Mikoriza Arbuskular dalam Mengendalikan Penyakit Busuk Pelepah pada Tanaman Jagung - Soenartiningsih Soenartiningsih (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2012)
Sheath blight disease is important disease on maize, it caused by Rhizoctonia solani. biological control using arbuscular mycorrhizal is assumed can reduce expansion of the soil borne disease. The experiment was carried out using arranged in completely randomized design of factorial, with different density spore and two isolate of AM fungus ie: Glomus sp and Acaulospora mellea. There were three replicates arbuscular mycorrhizal at 100-300 spore per 10-30 grams propagule was inoculated to each planting hole and inoculated R. solani fungi 30 days after planting. Sheath blight disease observation was taken 10-50 days after inoculation R. solani, while observation their  histology stalk and root at 50 days after inoculation of R. solani. The result of the experiment that inoculation  of AM fungus with 100-300 spore have potential to control sheath blight disease on maize. At the plant infected by AM fungi isolate of Glomus sp its emphasis reach of 21,9%–40,98%, while infected by A. mellea emphasis reach 21,48%–39,93%. The damage of stalk tissue at the plant infected by R. solani was more acute than at the plant infected by both R. solani and mycorrhizal fungus even they had the same symptom, that was an necrosis at their stalk tissue. The plant infected by R. solani and mycorrhizal fungus were not different with the root tissue of healthy plant.